Value Conflict in Bali's Casino Development Plan: Value Conflict Theory Analysis - Kapela, I Made Ari (Bali Tourism Board, 2025)
One of the most controversial issues that has sparked debate in print media is the proposal to develop casinos in Bali—a topic that resurfaced in mid-2024. This controversy reveals a deep conflict between two social groups: local government authorities and cultural communities advocating for the preservation of local values and a group of young entrepreneurs proposing a new economic approach. This proposal triggered a heated debate between proponents, who viewed casinos as economic catalysts, and opponents—including the Ministry of Tourism and the Bali Tourism Office. This study seeks to explore the public controversy surrounding the proposed development of casinos in Bali, with a particular focus on illustrating the conflict between economic interests and the preservation of culture-based tourism. This study employs a qualitative descriptive research design. Data collection is conducted through a literature review, drawing on existing academic works, media reports, and relevant public statements. The debate surrounding the proposal to establish international-standard casinos in Bali highlights a profound conflict between the preservation of traditional cultural values and aspirations for economic modernization. This conflict exemplifies the central thesis of Value Conflict Theory, which posits that societal disputes often arise from incompatible value systems rather than mere material interests. The opposing sides in Bali’s casino debate are not only advancing different economic strategies but are also championing divergent visions of what constitutes societal progress. The challenge lies in reconciling these distinct value frameworks without diminishing either side’s fundamental aspirations.